Interrupted E2F1-miR-34c-SCF negative feedback loop by hyper-methylation promotes colorectal cancer cell proliferation. Issue 1 (3rd February 2016) - Yang, Shu; Wu, Bo; Sun, Haimei; Ji, Fengqing; Sun, Tingyi; Zhao, Yan; Zhou, Deshan
Abstract : E2F1 promoted miR-34c transcription which reduced its target stem cell factor (SCF) and inhibited colorectal cancer (CRC) cell proliferation. While, SCF increased E2F1 production, suggesting an existence of E2F1-miR-34c-SCF negative feedback loop, which was interrupted by hyper-methylation of miR-34c promoter in CRC cells. Abstract : Tumour suppressor miR-34c deficiency resulted from hyper-methylation in its promoter is believed to be one of the main causes of colorectal cancer (CRC). Till date, miR-34c has been validated as a direct target of p53; but previous evidence suggested other transcription factor(s) must be involved in miR-34c transcription. In the present study, we in the first place identified a core promoter region (−1118 to −883 bp) of pre-miR-34c which was embedded within a hyper-methylated CpG island. Secondly, E2F1 promoted miR-34c transcription by physical interaction with the miR-34c promoter at site −897 to −889 bp. The transcriptional activating effect of E2F1 on miR-34c was in a p53 independent manner but profoundly promoted in the presence of p53 with exposure to 5-aza-2′-deoxycytidine (DAC). Thirdly, stem cell factor (SCF), a miR-34c target, was specifically reduced upon an introduction of E2F1 which lead to suppression of CRC cell proliferation. The E2F1-suppressed cell proliferation was partially abrogated by additional miR-34c inhibitor, indicating that the anti-proliferation effect of E2F1 was probably through activating miR-34c -SCF axis. Finally, SCF/KIT signalling increased E2F1 production by reducing its proteosomal degradation dependent on PI3K/Akt-GSK3β pathway. In conclusion, our results suggested the existence of E2F1- miR-34c -SCF negative feedback loop which was interrupted by the hyper-methylation of miR-34c promoter in CRC cells and increased cell proliferation.